Reprodução de papagaio-verdadeiro (Amazona aestiva) em cativeiro: perfil anual de esteróides sexuais e ensaio de estímulo hormonal exógeno - Christofoletti, Mauricio Durante [UNESP] (2014)
Brazil is the country with the greatest diversity of parrots in the world , with to 72 recognized species , with 16 species in the Red List of Endangered Brazilian Wild Animals . The blue-fronted amazon parrot ( Amazona aestiva ) stands out for its popularity as a pet , being collected from the wild in large numbers to attend the illegal market for wildlife. His captive breeding can become a tool for the conservation of populations in nature , but this requires a creation based on scientific knowledge and advanced breeding techniques . This thesis aimed to present the annual endocrine profile of sex steroids of Amazona aestiva and a test of hormonal stimulation by applying GnRH analogue of the slow release. It was used 10 couples and 4 adult males of Amazona aestiva kept in suspended cages, properties of the commercial breeder “Criadouro da Brisa”, located in Jaboticabal / SP. The droppings were collected at least once a week between June 2011 and July 2012 for the understanding of endocrine processes of the reproduction in this specie and between August 2012 and December 2012 for testing hormonal stimulation . The monitoring of gonadal activity was noninvasively by measuring androgen metabolites in droppings of males and females of droppings progestogens. Fresh droppings samples were collected , always in between 14h to 17h , and kept frozen until processing . The samples were dried at 57oC, crushed and hormones were extracted using 80% methanol . The hormone dosage was performed at the Laboratory of Endocrinology, NUPECCE ( Center for Research and Conservation of Deer ) using enzyme immunoassay with antibody to androgens and progestins . In exogenous hormone stimulation test with GnRH was applied analago buserelin slow release in 5 couples and 5 couples were used to control the following excreta collection , processing and hormonal dosage previously described . The results of the annual listing of androgens in males ...